Spatial Analysis of Water Infiltration Potential in the Miu Watershed of Sigi Regency - Amati Eltriman Hulu; Hasriani Muis; Sudirman Daeng Massiri; Naharuddin Naharuddin; Bau Toknok; Hendra Pribadi; Abdul Rahman; Arman Maiwa; Rhamdhani Fitrah Baharuddin; Muhammad Adam Suni; Nurul Istiqamah (Advance Sustainable Science Engineering and Technology, 2023)
Abstract. The sustainable management of the Miu watershed Basin is something that needs to be considered in line with the increasing complexity of environmental sustainability challenges and current water availability, not limited to maintaining the flow of water but need to pay attention to the balance of the ecosystem. Ecosystem conditions that are maintained influence high water absorption capacity, thereby reducing surface water runoff.. This research was conducted in the Miu watershed Basin with the aim of identifying the potential for water absorption, the method used in this study was a scoring method with four parameters, namely soil type, slope, rainfall, and land use. Data analysis was carried out using a Geographic Information System (GIS) approach. The results showed that the water absorption conditions in the Miu watershed Basin were classified as good (8.29%), normal good (73.91%), starting to be critical (14.51%), moderately critical (3.29%), and critical ( 0.00%).